Embolization of Brain Arteriovenous Malformations With Versus Without Onyx Before Stereotactic Radiosurgery. Issue 2 (29th August 2020) - Chen, Ching-Jen; Ding, Dale; Lee, Cheng-Chia; Kearns, Kathryn N; Pomeraniec, I Jonathan; Cifarelli, Christopher P; Arsanious, David E; Liscak, Roman; Hanuska, Jaromir; Williams, Brian J; Yusuf, Mehran B; Woo, Shiao Y; et al.
Abstract: BACKGROUND: Embolization of brain arteriovenous malformations (AVMs) using ethylene-vinyl alcohol copolymer (Onyx) embolization may influence the treatment effects of stereotactic radiosurgery (SRS) differently than other embolysates. OBJECTIVE: To compare the outcomes of pre-SRS AVM embolization with vs without Onyx through a multicenter, retrospective matched cohort study. METHODS: We retrospectively reviewed International Radiosurgery Research Foundation AVM databases from 1987 to 2018. Embolized AVMs treated with SRS were selected and categorized based on embolysate usage into Onyx embolization (OE + SRS) or non-Onyx embolization (NOE + SRS) cohorts. The 2 cohorts were matched in a 1:1 ratio using de novo AVM features for comparative analysis of outcomes. RESULTS: The matched cohorts each comprised 45 patients. Crude AVM obliteration rates were similar between the matched OE + SRS vs NOE + SRS cohorts (47% vs 51%; odds ratio [OR] = 0.837, P  = .673). Cumulative probabilities of obliteration were also similar between the OE + SRS vs NOE + SRS cohorts (subhazard ratio = 0.992, P  = .980). Rates of post-SRS hemorrhage, all-cause mortality, radiation-induced changes, cyst formation, and embolization-associated complications were similar between the matched cohorts. Sensitivity analysis for AVMs in the OE + SRS cohort embolized with Onyx alone revealed a higher rate of asymptomatic embolization-associated complications in this subgroup compared to the NOE + SRS cohort (36% vs 15%; OR = 3.297, P  = .034), but the symptomatic complication rates were similar. CONCLUSION: Nidal embolization using Onyx does not appear to differentially impact the outcomes of AVM SRS compared with non-Onyx embolysates. The embolic agent selected for pre-SRS AVM embolization should reflect both the experience of the neurointerventionalist and target of endovascular intervention.